Violence against Women by Addicted Husbands in Iraq - Al-Musawy, jasim; Nashtar, Saad Badai; Hussein, Hassan Sayid; Rajjoub, Rahaf Akel; Jazan, Hadi Faiz; Kadhum, Abdul Amir H. (Open Access Macedonian Journal of Medical Sciences, 2022)
Objective: Despite that women are becoming active participants and protagonists of the development social, economic, and political process, they still suffer from the distress of violence, and this problem still spread worldwide. Domestic violence against women is studied in the general population, but the violence against women with addicted spouses was little highlighted especially in Iraq, and this study aimed to reveal the rate of violence and to clarify the different types of violence against wives of addicted husbands. Methods: This comparative study was carried in Ibn Rushud psychiatric training hospital in Baghdad, Iraq This study has been done during the time extended from10th April to 20thof December 2020, and conducted on 400 married women,200 of them were women with addicted husbands, and200were women with no addicted husband. The inclusion criteria were married women living with her husband, and those women who voluntarily gave consent were included. Divorced widows and pregnant women are excluded. The questionnaire used was valid and reliable and appropriate to our society's culture furthermore it was used in a similar study done in the neighboring country. Data analysis was performed using SPSS. Descriptive statistics and chi-square, Mann-Whitney U, and Kruskal–Wallis tests, odds ratio (OR), and Kendall's correlation coefficient were used to analyze the data. The overall mean score of violence was 70.47 ± 14.32 for the women with addicted husbands and 42.01 ± 7.50 for women with non-addicted spouses (P < 0.001). The mean score of psychological violence was 40.03 ± 5.03 in women with addicted spouses and 23.40 ± 4.26 in those with non-addicted husbands (P < 0.001). Furthermore, the mean score of physical violence was 23.71 ± 6.24 in women with addicted spouses and 15.50 ±3.76 in those with non-addicted husbands (P < 0.001). Moreover, the mean scores of sexual violence were 3.21 ± 2.11 and 2.92 ± 0.25 in women with and without addicted spouses, respectively (P < 0.001). Finally, the mean scores of financial violence were 2.10±0.94and 1.10 ± 0.23 for women with and without an addicted husband, respectively (P<0.001). Result: The finding confirms the conclusion of other studies and reveals that the overall rate of violence was significantly higher among women with addicted spouses and especially if the spouse abused more than one type of substance.